On Semiannahilator Supplement Submodules - Helal, Layla H.; Yaseen, Sahira M. (Iraqi Journal of Science, 2020)
Let R be associative; ring; with an identity and let D be unitary left R- module; . In this work we present semiannihilator; supplement submodule as a generalization of R-a- supplement submodule, Let U and V be submodules of an R-module D if D=U+V and whenever Yâ‰¤ V and D=U+Y, then annYâ‰ªR;. We also introduce the the concept of semiannihilator -supplemented ;modules and semiannihilator weak; supplemented modules, and we give some basic properties of this conseptes.